2010
DOI: 10.1007/s10557-010-6252-x
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridamole with Low-Dose Aspirin Augments the Infarct Size-Limiting Effects of Simvastatin

Abstract: PurposeStatins protect against ischemia-reperfusion injury and limit myocardial infarct size (IS). This effect is dependent on increased generation of adenosine by ecto-5′ nucleotidase and downstream activation of cyclooxygenase-2 (COX2). Dipyridamole (DIP) augments the IS-limiting effects of statins by blocking the cellular reuptake of adenosine; whereas aspirin (ASA) attenuates the effect by inhibiting COX2. We studied the effect of acute administration of DIP, ASA and their combination on the IS-limiting ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 33 publications
2
20
0
1
Order By: Relevance
“…Blockade of COX-2 can abolish the cardioprotective phenomena, most importantly delayed or second window preconditioning (Przyklenk and Heusch, 2003;Huhn et al, 2009a;Guo et al, 2012). High-dose aspirin, which blocks both COX-1 and COX-2, interferes with endogenous cardioprotection (Ye et al, 2010b). Nevertheless, many patients with an acute MI receive high-dose aspirin (.300 mg) orally or intravenously.…”
Section: G Cyclooxygenase Inhibitorsmentioning
confidence: 99%
“…Blockade of COX-2 can abolish the cardioprotective phenomena, most importantly delayed or second window preconditioning (Przyklenk and Heusch, 2003;Huhn et al, 2009a;Guo et al, 2012). High-dose aspirin, which blocks both COX-1 and COX-2, interferes with endogenous cardioprotection (Ye et al, 2010b). Nevertheless, many patients with an acute MI receive high-dose aspirin (.300 mg) orally or intravenously.…”
Section: G Cyclooxygenase Inhibitorsmentioning
confidence: 99%
“…Only high-dose aspirin that blocks both cyclo-oxygenase 1 and 2 seems to interfere with cardioprotection. 215,216 While a patient with coronary artery disease who suffers an AMI or undergoes a cardiovascular intervention will likely have one or more of the above drugs on board, nitrates, opioids, and purinergic receptor 2Y 12 (P2Y 12 ) antagonists would be administered acutely to induce coronary vasodilation and control blood pressure, to reduce pain, and to inhibit platelet aggregation. Although chronic nitrate use and nitrate tolerance abrogate protection by conditioning interventions, 217,218 the acute use of nitrates during surgical coronary revascularization does not interfere with protection by remote ischemia preconditioning.…”
Section: Lack Of Comorbidities and Comedications In Animal Experimentsmentioning
confidence: 99%
“…18,27,28 We found that the IS-limiting effect of ticagrelor was abrogated with CGS15943, an adenosine-receptor antagonist, whereas CGS15943 alone or in combination with clopidogrel had no effect (Figure 2). Moreover, CGS15943 abolished ticagrelorinduced upregulation of cNOS, cPLA 2 , and COX2 activities (Figure 3), upregulation of Akt and eNOS phosphorylation, …”
mentioning
confidence: 94%
“…16,17 For instance, statins activate ecto-5′ nucleotidase that converts AMP into adenosine 18 , and the IS-limiting effect of statins is dependent on adenosine-receptor activation. 18,27,28 We found that the IS-limiting effect of ticagrelor was abrogated with CGS15943, an adenosine-receptor antagonist, whereas CGS15943 alone or in combination with clopidogrel had no effect (Figure 2). Moreover, CGS15943 abolished ticagrelorinduced upregulation of cNOS, cPLA 2 , and COX2 activities (Figure 3), upregulation of Akt and eNOS phosphorylation, and upregulation of COX2 mRNA levels ( Figure 4).…”
mentioning
confidence: 94%